45 Patient and clinician interventions for opioid analgesic deprescribing in chronic non-cancer pain: a systematic review. (4th December 2019) - Mathieson, Stephanie; Maher, Christopher; Ferreira, Giovanni; Hamilton, Melanie; Jansen, Jesse; McLachlan, Andrew; Underwood, Martin; Lin, Chung-Wei Christine
Abstract : Background: Deprescribing, the process of reducing or discontinuing unnecessary or harmful medicines, is an essential part of clinical practice. Previous reviews assessing opioid analgesic deprescribing strategies in chronic pain have been inconclusive due to the limited number of studies or focused on long-term opioid therapy. Objectives: To investigate interventions aiming to reduce/cease opioid analgesic prescription or use in people with chronic pain. The primary outcome was the mean reduction in daily opioid analgesic dose (morphine milligram equivalent (mg/day)). Secondary outcomes included the reduction of opioid prescriptions, the proportion who reduced or ceased, serious adverse events and adverse events, and change in pain intensity, disability and quality of life. Methods: We searched electronic databases and clinical trial registries with no restrictions. We included randomised controlled trials (RCTs) evaluating interventions to reduce/cease opioid analgesic prescription or use in patients with chronic pain versus usual care or control. Two authors independently screened and extracted data. Outcome follow-up time points were short (≤ 3 months), intermediate (> 3 but < 12 months) or long (≥ 12 months) term. Primary outcome was reduction in opioid dose (morphine milligram equivalent (MME) mg/day). Methodological quality was assessed using the Cochrane Risk of Bias tool. Study heterogeneity prevented pooling. Results: We included 12 RCTs; 10 trials tested patient-focused interventions (N = 866 chronic pain patients) (e.g. discontinuation protocol or cognitive behavioural therapy) and 2 testing clinician-focused interventions (N = 291 clinicians) (e.g. education). RCTs were typically small (median = 35 chronic pain participants). Patient interventions showed no effect on opioid use e.g. a discontinuation protocol did not reduce the daily dose (mean difference (MD) -19.91 MME/day, 95%CI -107.50 to 67.68) or cease opioid use (risk difference (RD) 0.00, 95%CI -0.15 to 0.16) at intermediate-term. However, there was no increase in the risk of serious adverse events or adverse events. Small reductions were observed in the number of opioid prescriptions (RD -0.11, 95%CI -0.17 to -0.05) and the number of participants who reduced their use (RD -0.07, 95%CI -0.12 to -0.01) at long-term in one clinician intervention of education plus decision tools versus decision tools alone. Conclusion: The small number of studies and heterogeneity prevented any firm conclusions on any opioid analgesic deprescribing strategy being made. There is insufficient evidence to be able to recommend to clinicians any one particular method to deprescribe opioid analgesic medicines in patients with chronic non-cancer pain.